Autonomous Learning during COVID-19 Pandemic: Students’ Objectives and Preferences - Ariebowo, Teguh (Journal of Foreign Language Teaching and Learning, 2021)
Students’ voices remain one of the essential sources to evaluate and develop learning materials in which students as the center. This study attempts to evaluate the current English teaching and learning process in a school of aerospace technology. The researcher felt the urge to evaluate it since the teaching and learning process suddenly turned the direction into online learning due to the COVID-19 pandemic globally. Specifically, this study explored the students’ objectives and preferences in learning English during the current situation. Initially, the researcher asked students in one of his classes randomly to be interviewed as the study's preliminary data. A questionnaire was developed from the interview to survey all students of his classes, with 166 students in total. Besides interviews and questionnaires, the data were also collected from the documentation owned by the academic affairs. From the data, it was found that students were basically aware of their learning objectives that corresponded positively to the curriculum developer's objectives. Their preferences in online learning showed how autonomous they were as English learners. However, some findings from the documentation indicated criticism to the teachers that revealed another learner autonomy level.